Investigations into metabolism, transport and function of sulfonated steroids in the porcine testicular-epididymal compartment - Dezhkam, Yaser; Justus Liebig University Giessen (My University, 2015)
Sulfonated steroids have been traditionally regarded as inactive metabolites destined for excretion, as they are incapable of binding to classical nuclear steroid receptors. However, by the enzyme steroid sulfatase (STS) they may be converted into free steroids, which may be biologically active directly or after a few additional enzymatic reactions. Thus, as sulfonated steroids commonly circulate at relatively high concentrations, they may form an important pool of precursors for the local (intra-tissue) production of active free steroids. This so-called sulfatase pathway has received increased attention over recent years especially with respect to estrogen metabolism in human hormone-dependent breast cancer, where the intratumoral estrogen production from sulfonated precursors obviously has a much higher capacity in comparison to the de novo synthesis via free steroids. This study is composed of two parts of which the first one addresses the secretory patterns of free and sulfonated steroids in vivo, whereas in the second part the expression of STS and of the steroid sulfotransferases SULT1E1 (estrogen specific) and SULT2B1 (specific for beta-hydroxysteroids) was characterized in the testis and in different segments of the epididymis. Other subjects of the second part of this study were hydrolysis of steroid sulfates and the sulfonation of estrone (E1), dehydroepiandrosterone (DHEA) and pregnenolone (P5) in the tissues investigated.Concentrations of androstenedione, testosterone, pregnenolone sulfate (P5S), dehydroepiandrosterone sulfate (DHEAS), estrone-3-sulfate (E1S)and 17beta-estradiol-3-sulfate were performed in the Steroid Research & Mass Spectrometry Unit, Division of Pediatric Endocrinology & Diabetology, Center of Child and Adolescent Medicine, Justus-Liebig-University, Giessen (head: Prof. Dr. S. Wudy) applying liquid chromatography tandem mass spectrometry (LC-MS-MS). Moreover, 17beta-estradiol (E2) and E1 were measured by inhouse radioimmunoassays to cope with the low concentrations of free estrogens in boars.In order to get new information on the sulfonation of free steroids and the hydrolysis of steroid sulfates in the porcine testicular-epididymal compartment, subcellular fractions were prepared from tissue samples collected from the testis and from defined sites of the epididymis (EH1, EH2: proximal/distal part of epididymal head; EB1-4: epididymal body, from proximal to distal; ET1, ET2: proximal/distal part of epididymal tail) using differential centrifugation. STS and steroid sulfotransferase activities were measured based on the differential distribution of free and sulfonated steroids between an aqueous phase and an organic solvent, tert butyl-methylether.The immunostaining results were shown that SULTs 1E1 and 2B1, immunostaining was especially prominent in superficial epithelial protrusions. Sporadic staining of weaker intensity was also found in the muscular layer and in the vascular endothelium. With WB, a specific band of the expected molecular size (approx. 61 kDa) was found in the testis and all segments of the epididymis. These results show that STS is widely expressed in the porcine testicular-epididymal compartment, indicating a high potential for sulfatase pathways especially in Leydig cells and the epithelial cells of the rete testis and epididymis. The co-expression of STS with SULTs 1E1 and 2B1 in the epididymal epithelium and especially their colocalization in superficial protrusions are very intriguing. In the epididymal duct, apocrine secretion has been described to give rise to the formation of epididymosomes, small vesicles which are considered as vehicles for the transfer of certain molecules to the maturing sperm cells. Other intriguing findings are the virtual absence of a sulfonation of E1, DHEA and P5 in testicular cytosols as well as the absent or questionable detection of SULTs 1E1 and 2B1 in light of the high efflux of various steroid sulfates from the testis. A plausible explanation could be a significant use of sulfonated steroids as precursors/intermediates in porcine testicular steroidogenesis starting from cholesterol sulfate. The concept of a sulfate pathway of steroidogenesis would not only provide an explanation for the production of high amounts of steroid sulfates in the virtual absence of relevant steroid sulfotransferase activities but also for the high STS expression in Leydig cells. According to this concept, STS could play a crucial role in the control of the substrate flow through the steroidogenic enzyme cascade by mediating the transition of sulfonated precursors into the pool of free steroids, with the exact subcellular localization being of importance for the step of the enzyme cascade at which this transition(s) may occur. Thus, in order to corroborate this concept investigations into the utilization of sulfonated substrates by steroidogenic enzymes and on the subcellular localization of STS are necessary.
Keywords: solfunated steroids; boar; ddc:630